Sympathetic nerve block as an add-on therapy for intervention and prevention of cerebral vasospasm after subarachnoid hemorrhage - Zhaoquan Wang; Jianqiang Li (Frontiers in Neurology)
Cerebral vasospasm is a major complication after subarachnoid hemorrhage (SAH) and is an important factor leading to disability and mortality in patients. Cerebral vasospasm involves cerebral artery stenosis and leads to delayed cerebral ischemia, further exacerbating brain damage. The pathophysiology of cerebral vasospasm is multifactorial, involving a complex interaction between fragmented red blood cell metabolism, endothelial dysfunction, and hyperresponsive contraction of smooth muscle cells. Recent studies have highlighted the important role of the sympathetic nervous system (SNS) in mediating and exacerbating cerebral vasospasm. Sympathetic activation affects vascular tone and contributes to the development of vasospasm after SAH. Stellate ganglion block (SGB) has been reported to have a protective effect in patients at risk for vasospasm after SAH due to reduced sympathetic activity. This review aims to explore the current understanding of the relationship between sympathetic activity and cerebral vasospasm, investigate the molecular mechanisms involved, clinical implications, and potential therapeutic strategies targeting sympathetic modulation.